Media Promises - Ben Anderson (Media Theory)
In this essay, I argue that Lauren Berlant’s work poses the question of how and to what we are attached by and through our media and popular culture. Beginning from a scene of listening, and juxtaposing it throughout the piece with the popular culture of romantic love, the piece encounters Berlant as a thinker of the movement of attaching-detaching. Attachment is a special type of relation, through which an ‘object’ becomes promissory. The first part of the essay summarises Berlant’s theorising of ‘attachment’ and argues that media and popular cultures circulate and distribute ‘promises’ that serve as resources to organise and intensify attachments. It then shifts to the importance of detaching and detachment in Berlant’s writings, arguing that detachment is the ever-present condition and accompaniment for attachment. As media circulate and distribute promises that are enacted through popular cultures, they simultaneously detach and (re)produce detachments. In conclusion, I advocate for a media theory that centres the dynamics of attaching-detaching and performs Berlant’s ethical-political imperative and methodological call to not shame people’s attachments.